Incidental MRI lesions suggestive of multiple sclerosis in asymptomatic patients in Karachi, Pakistan. Issue 1 (22nd October 2010) - Wasay, M; Rizvi, F; Azeemuddin, M; Yousuf, A; Fredrikson, S
Abstract : The objective of this study was to identify asymptomatic patients with brain MRI lesions suggestive of multiple sclerosis (MS) in a low-prevalence area of Pakistan. Brain MRIs for 864 patients were reviewed at the Aga Khan University (Karachi, Pakistan) during an 8-month period of 2006 and 2007 to identify patients with lesions suggestive of MS. The lesions were characterised based on modified Barkhof criteria. Six (two females) (0.7%) of 864 patients fulfilled brain MRI criteria suggestive of MS. The mean number of MRI lesions (total lesions on T2) were 9 (range 5–14). Although Pakistan is considered a low-prevalence area for MS, 0.7% of brain MRI scans in patients without clinical MS symptoms showed lesions fulfilling brain MRI criteria of MS.